Collaboration, Coordination, and Cooperation Among Organizations: Establishing the Distinctive Meanings of These Terms Through a Systematic Literature Review - Castañer, Xavier; Oliveira, Nuno (Journal of Management, 2020)
Collaboration, coordination, and cooperation lie at the core of interorganizational activities. To address the confusion regarding the definitions of these three terms, recent works have proposed redefinitions. Although these proposals address an important concern, we believe that they might be premature because (1) they do not build on a systematic examination of how these terms have been used in the literature and (2) they seem to narrow the focus to a given theory and alliances only, which might unduly restrict the meaning of the terms defined. In this paper, we review the definitions of the three terms as they appear in nine top journals in the general management literature (1948-2017). By studying the definitions, we identify three interactional dimensions that are present to different extents in collaboration, coordination, and cooperation: attitude, behavior, and outcome. Our systematic review confirms the confusion and lack of parsimony in the extant definitions. The overlap in the content of these dimensions across the three terms does not provide a basis for distinctively defining collaboration, coordination, and cooperation. Thus, we further draw on our review to identify two discriminating dimensions that allow us to distinguish these three terms: the temporal stage and the type of goal. Our review contributes to theoretical development by offering a conceptual redefinition of the three terms that renders them distinct and thus facilitates knowledge accumulation and theory development. Moreover, the set of interactional and discriminating dimensions generates a host of managerially relevant research questions about a wide range of interorganizational relationships.